Subjects of civil obligation - Слома, Валентина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
One of the important elements of the proper functioning of the market economy in Ukraine is civil liability. In this context it is necessary to study not only the concept and the grounds of civil legal obligations, but the subject composition of this legal relationship. Obligation relationships consist of three elements: a subject, an object and a content (subjective civil law and subjective civil obligation). In general the obligation involves a debtor and a creditor. However, there are situations when there are some people as the creditors or the debtors. In this case we should speak about the plurality of individuals. Obligations with the plurality of subjects are divided into: active, passive and mixed. Active plurality of the obligations can be found in the creditors’ side, passive plurality is congenial for the side of the debtors, and mixed one provides multiple entities for both the creditors and the debtor side. In the contractual obligations the contractors deal with all sorts of relationships among certain entities, which are called "other parties". None of them is being the party, but their actions somehow affect the dynamics of the legal relationships, including contract, referred to as "the third parties". Civil law suggests various forms of participation of the third parties in the process. In particular, the third parties can be attributed to the circle of liability in case of forwarding performance of the obligation. Civil law also supposes the obligation of the debtor by the third party. The third parties may participate in the so-called recourse liabilities. Recourse obligation is the obligation, the content of which is the reverse of the recovery of money or property, made by one person on behalf of another, or because of the fault of the latter to the third parties. While carrying out the obligation it is permitted to replace the obligation of the parties due to the law. According to the will of the subject the ways of changing the obligation can be divided into the following types: the will of the creditor (assignment, succession); the will of the debtor (debtor’s transaction of the obligation to another person, succession); mutual agreement of the debtor and the creditor (treaty to replace the debtor in the obligation); the will of the third parties liable under the interim agreement (the obligation of the debtor as a guarantor (property guarantor)); the will of others, delay in performing the obligation of the debtor under the threat of losing his rights for property. The subjects of civil obligations are their parties (a lender and a borrower), others on the side of the debtor (or) a creditor and a third party. It should be noted that the study of the legal status of civil legal obligations is not limited by this article and shall be subject to further research.